Juridical Analysis Of Handling Beggers And Budgets In East Jakarta - Nurmala Sari; Ardiansyah, Ardiansyah (Fox Justi : Jurnal Ilmu Hukum, 2024)
Handling beggars and homeless people in East Jakarta is one of the policy focuses implemented by the East Jakarta Social Service in an effort to create social welfare for the community. Even though various policies and programs have been implemented, the problem of beggars and homelessness remains a serious challenge for local governments. This research aims to analyze provisions for dealing with the problems of beggars and homelessness, as well as assessing the effectiveness, challenges and impact of these policies. The formulation of the problem is: What are the legal regulations for dealing with beggars and homeless people? And what is the evaluation and monitoring mechanism for the implementation of these regulations? The research results show that the East Jakarta Social Service's policies tend to focus more on short-term control and pay less attention to long-term empowerment aspects for the individuals involved. Therefore, the recommendations from this research include the need for more comprehensive policies, with a more humane approach and based on socio-economic empowerment, as well as increased collaboration between institutions to deal with this problem more holistically.